2017
DOI: 10.1371/journal.pone.0185285
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal changes in the distribution of LHFPL5 in mice cochlear hair bundles during development and in the absence of PCDH15

Abstract: Mechanosensory transduction by vertebrate hair cells depends on a protein complex at the tips of shorter stereocilia associated with mechanoelectrical transduction channels activated by tip links in the hair bundle. In mammalian hair cells, this complex includes transmembrane channel-like protein subunit 1 (TMC1), lipoma HMGIC fusion partner-like 5 protein (LHFPL5) and protocadherin 15 (PCDH15), a lower-end component of the tip link. TMC1 interacts with LHFPL5 and PCDH15 but how the complex develops to maturit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 24 publications
6
39
0
Order By: Relevance
“…We have presented the following findings ( Fig. 10): 1) TMC1 and LHFPL5 predominantly localize at the tip of the shorter rows of stereocilia in neonatal hair cells, which largely verifies previous findings in neonatal hair cells (7,9); 2) LHFPL5 persists in the hair bundle of hair cells after P7, which clarifies the unexplained absence of LHFPL5 after P7 previously reported (7,10) and supports the notion that LHFPL5 is a permanent component in the MT complex; 3) TMC1 remains at the tip of the shorter rows of stereocilia in adult OHCs but is uniformly distributed in both the tallest row and the shorter rows of stereocilia in adult IHCs; and 4) LHFPL5 remains at the tip of the shorter rows of stereocilia in adult OHCs but is uniformly distributed in the shorter rows of stereocilia in adult IHCs. The unexpected uniform distribution of TMC1 and LHFPL5 in the hair bundle of adult IHCs raises intriguing questions regarding the 2 proteins' turnover rates, regulations, additional functions, and functional interactions.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We have presented the following findings ( Fig. 10): 1) TMC1 and LHFPL5 predominantly localize at the tip of the shorter rows of stereocilia in neonatal hair cells, which largely verifies previous findings in neonatal hair cells (7,9); 2) LHFPL5 persists in the hair bundle of hair cells after P7, which clarifies the unexplained absence of LHFPL5 after P7 previously reported (7,10) and supports the notion that LHFPL5 is a permanent component in the MT complex; 3) TMC1 remains at the tip of the shorter rows of stereocilia in adult OHCs but is uniformly distributed in both the tallest row and the shorter rows of stereocilia in adult IHCs; and 4) LHFPL5 remains at the tip of the shorter rows of stereocilia in adult OHCs but is uniformly distributed in the shorter rows of stereocilia in adult IHCs. The unexpected uniform distribution of TMC1 and LHFPL5 in the hair bundle of adult IHCs raises intriguing questions regarding the 2 proteins' turnover rates, regulations, additional functions, and functional interactions.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to what was reported by Xiong et al (10) again found that LHFPL5 labeling declined substantially by P6, although the labeling remained detectable at the tip of very few shorter rows of stereocilia at P21. We speculate that the marked reduction in LHFPL5 detection in this study is also a consequence of the dynamic change of antibodyepitope accessibility.…”
Section: Localization Of Lhfpl5 In Hair Cells Before and After P7supporting
confidence: 88%
See 2 more Smart Citations
“…For example, PCDH15 largely requires LHFPL5 for trafficking to the stereocilia [17, 18, 38], and depends on Cadherin 23 to maintain its localization at the site of MET [17, 39]. LHFPL5 also requires PCDH15 to maintain localization at the stereocilia tips [18, 38]. Thus, Tmie appears to be the exception to the rule of co-dependent transport to the hair bundle.…”
Section: Discussionmentioning
confidence: 99%